Venous and arterial thrombosis in dialysis patients - Ocak, Gurbey; Vossen, Carla Y.; Rotmans, Joris I.; Lijfering, Willem M.; Rosendaal, Frits R.; Parlevliet, Karien J.; Krediet, Ray T.; Boeschoten, Els W.; Dekker, Friedo W.; Verduijn, Marion (Thrombosis and Haemostasis, 2011)
Whether the risk of both venous and arterial thrombosis is increased in dialysis patients as compared to the general population is unknown. In addition, it is unknown which subgroups are at highest risk. Fur-thermore, it is unknown whether having a history of venous thrombosis or arterial thrombosis prior to dialysis treatment increases mortality risk. A total of 455 dialysis patients were followed for objectively verified symptomatic thrombotic events between January 1997 and June 2009. The incidence rates in dialysis patients as compared to the general population was 5.6-fold (95% CI 3.1–8.9) increased for venous thrombosis, 11.9-fold (95% CI 9.3–14.9) increased for myocardial infarction, and 8.4-fold (95% CI 5.7–11.5) increased for ischaemic stroke. The combination of haemodialysis, lowest tertile of albumin, history of venous thrombosis, and malignancy was associated with subsequent venous thrombosis. Increased age, renal vascular disease, diabetes, high cholesterol levels, history of venous thrombosis, and history of arterial thrombosis were associated with subsequent arterial thrombosis. The all-cause mortality risk was 1.9-fold (95% CI 1.1–3.3) increased for patients with a history of venous thrombosis and 1.9-fold (95% CI 1.4–2.6) increased for patients with a history of arterial thrombosis. A potential limitation of this study was that in some risk categories as-sociations with venous thrombosis did not reach statistical significance due to small numbers. In conclusion, dialysis patients have clearly elev-ated risks of venous thrombosis and arterial thrombosis and occurrence of venous thrombosis or arterial thrombosis prior to the start of dialysis is associated with an increased mortality risk.
Keywords: Dialysis; venous thrombosis; arterial thrombosis